Challenging DESs and ILs in the valorization of food waste: a case study - Mero, Angelica; Moody, Nicholas R.; Husanu, Elena; Mezzetta, Andrea; D’Andrea, Felicia; Pomelli, Christian Silvio; Bernaert, Nathalie; Paradisi, Francesca; Guazzelli, Lorenzo (Frontiers in Chemistry, 2023)
In this study, the efficacy effect of two of the best performing green solvents for the fractionation of lignocellulosic biomass, cholinium arginate (ChArg) as biobased ionic liquid (Bio-IL) and ChCl:lactic acid (ChCl:LA, 1:10) as natural deep eutectic solvent (NADES), was investigated and comparedwere tested in the pretreatment of an agri-food industry waste, apple fibers (90 °C for 1 h). For the sake of comparison, 1-butyl-3-methylimidazolium acetate (BMIM OAc) as one of the best IL able to dissolve cellulose was also used. After the pretreatment, two fractions were obtained in each case. The results gathered through FTIR and TGA analyses of the two materials and the subsequent DNS assay performed after enzymatic treatment led to identify ChArg as the best medium to delignify and remove waxes, present on the starting apple fibers, thus producing a material substantially enriched in cellulose (CRM). Conversely, ChCl:LA did not provide satisfactorily results using these mild conditions, while BMIM OAc showed intermediate performance probably on account of the reduced crystallinity of cellulose after the dissolution-regeneration process. To corroborate the obtained data, FTIR and TG analyses were also performed on the residues collected after the enzymatic hydrolysis. At the end of the pretreatment, ChArg was also quantitatively recovered without significant alterations.